1972
DOI: 10.1104/pp.49.4.490
|View full text |Cite
|
Sign up to set email alerts
|

Postillumination Respiration of Maize in Relation to Oxygen Concentration and Glycolic Acid Metabolism

Abstract: Prior illumination in C02-free air enhances a respiration from maize (Zea mays L.) leaves different in onset and duration from the postillumination burst of photorespiration. Respiration of attached leaves during the dark-light-dark sequence of the experiment was measured by infrared gas analysis of CO2 efflux from leaves at 25 ± 1 C into CO2-free N2 containing 0.04%, 2.23%, or 40% 02, or into C02-free air in an acrylic plastic chamber. Rapid flushing at 10 1 min-' replaced air by other gas mixtures.Respiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The reduction of leaf respiration after a period of photosynthesis at 1% O 2 , as we recorded for all species examined (Fig. 1), is consistent with earlier observations for Z. mays recorded by Heichel (1970Heichel ( , 1972. The decrease in post-illumination respiration could result from the limitation of oxygen diffusion into the leaf cells from an atmosphere with low O 2 , which could diminish the activity of the alternative respiratory pathway (Ribas-Carbo et al, 1994) which is also present in C 4 leaf mitochondria (Gardeström and Edwards, 1983;Stewart et al, 1990).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The reduction of leaf respiration after a period of photosynthesis at 1% O 2 , as we recorded for all species examined (Fig. 1), is consistent with earlier observations for Z. mays recorded by Heichel (1970Heichel ( , 1972. The decrease in post-illumination respiration could result from the limitation of oxygen diffusion into the leaf cells from an atmosphere with low O 2 , which could diminish the activity of the alternative respiratory pathway (Ribas-Carbo et al, 1994) which is also present in C 4 leaf mitochondria (Gardeström and Edwards, 1983;Stewart et al, 1990).…”
Section: Discussionsupporting
confidence: 87%
“…The CO 2 requirement was not greater than endogenous fixation, while the substrate for respiration, produced in the light, required oxygen for subsequent oxidation in darkness. Unexpectedly, the photorespiratory intermediates (glycolate, glyoxalate or glycine) fed to Z. mays leaves, in which the photorespiration is apparently absent, also doubled or tripled the respiration rate in darkness (Heichel, 1972). Further studies of the effect of light or metabolites on respiration in C 4 plants, particularly in species other than Z. mays, have not been undertaken to date.…”
Section: Introductionmentioning
confidence: 97%
“…In plant species with well-developed bundle sheaths, glycolate oxidase activity is greater in these cells than in the mesophyll cells (54,55). Maize leaves oxidized glycolate supplied in darkness, but the rate of CO 2 production was not rapid in relation to rates of photorespiration in iJ~efficient photosynthetic species (145).…”
Section: The Oxidation Of Glycolatementioning
confidence: 99%
“…Kylin el al. (1972), Heichel (1972) and Orr el at. (1976) have shown that the effect of DCMU on photosynthesis, growth and motility in photosynthetic organisms may vary with the concentration of DCVIU.…”
Section: Discussionmentioning
confidence: 99%
“…Kylin et al (1972) used diderent concentrations of DCMU to map different sites of photophosphorylation in Scenedesmus. Leaves of maize supplied with glycolic acid and treated with DCMU released more COî nto COj-frce atmosphere in bright light than did controls without DCMU fed with glycolic acid (Heichel 1972 al. (1976) showed that low concentrations of DCMU ( 10"^ M) reduced the motile/non-motile balance in Euglena populations.…”
Section: Introductionmentioning
confidence: 99%